Nanoscale mapping of electric polarizability in a heterogeneous dielectric material with surface irregularities. (6th October 2021) - Wang, Shaojie; Luo, Zhen; Liang, Jiajie; Peng, Simin; Hu, Jun; He, Jingliang; Li, Qi
Abstract: Nanoscale mapping of electric polarizability in a heterogeneous dielectric material with surface irregularities is of scientific and technical significance, but remains challenging. Here, we present an approach based on intermodulation electrostatic force microscopy (EFM) in conjunction with finite element computation for precise and high-resolution mapping of polarizability in dielectric materials. Instead of using electrostatic force in conventional quantitative EFM approaches, the force gradient is acquired to achieve an unprecedented spatial resolution. In the meantime, the finite element model is applied to eliminate the interference from the heterogeneity and surface irregularity of the sample. This approach directly reveals the high polarization ability of the amorphous region in a ferroelectric, semi-crystalline polymer with significant surface roughness, i.e. poly (vinylidene fluoride-co-chlorotrifluoroethylene), in which the result is consistent with the predicted data in the latest research. This work presenting a quantitative approach to nanoscale mapping of electric polarizability with unprecedented spatial resolution may help to reveal the complex property-structure correlation in heterogeneous dielectric materials.